The Overlooked Tradition of “Personal Music” and Its Place in the Evolution of Music - Nikolsky, Aleksey; Alekseyev, Eduard; Alekseev, Ivan; Dyakonova, Varvara (Frontiers in Psychology, 2020)
This is an attempt to describe and explain so-called timbre-based music as a special system of musicking, communication, and psychological and social usage, which along with its corresponding beliefs constitutes a viable alternative to “frequency-based” music. Unfortunately, the current scientific research into music has been skewed almost entirely in favor of the frequency-based music prevalent in the West. Subsequently, whenever samples of timbre-based music attract the attention of Western researchers, these are usually interpreted as “defective” implementations of frequency-based music. The presence of discrete pitch is often regarded as the structural criterion that distinguishes music from non-music. We would like to present evidence to the contrary—in support of the existence of indigenous music systems based on the discretization and patterning of aspects of timbre, rather than pitch. This evidence comes mainly from extensive ethnographic research systematically conducted in eastern European and Asian parts of Russia from the 1890s. It involved the efforts of thousands of specialists and was coordinated by dozens of research institutions, and it has included not just ethnomusicology but linguistics, philology, organology, archaeology, anthropology, geography, and religious and social studies. Much of the data has not been translated into Western languages. Timbre-based tonal organization (TO) differs from that based on frequency in its personal orientation: musicking here occurs primarily for oneself and/or for close relatives/friends. Collective music-making is rare and exceptional. The foundation of timbre-based music seems to have vocal roots and rests on “personal song”—a system of personal identification through individualized patterns of rhythm, timbre, and pitch contour, utilized like a “human voice”—whose sound enables the recognition of a particular individual. The instrumental counterpart of the personalized singing tradition is the jaw harp tradition. The jaw harp is the principal musical instrument for at least 21 ethnicities in Russia, who occupy over half the territory of the country. The evolution of its TO forms the backbone for the development of timbre-based music art. Here, we provide the acoustic, socio-cultural, geographic, and chronological overview of timbre-based music.